Antimicrobial Activity of Cotinus coggyria from Turkey - DULGER, BASARAN; HACIOGLU, NURCIHAN; BILEN, S. (Asian Journal of Chemistry, 2010)
Ethanolic extract obtained from Cotinus coggyria Scop. was investigated for its antimicrobial activity against Bacillus cereus, Bacillus subtilis, Staphylococcus aureus, Micrococcus luteus, Escherichia coli, Enterobacter aerogenes, Proteus vulgaris, Pseudomonas aeuginosa, Pseudomonas putida, Salmonella typhimurium, Salmonella typhi, Hanseniaspora guilliermondii, Rhodotorula rubra, Kluyveromyces fragilis, Kluyveromyces marxianus, Debaryomyces hansenii, Candida utilis and Candida albicans by disc diffusion method. The extracts had strong antimicrobial activity against bacteria, but weak activity was observed against the yeast cultures used in this study.